Pengaruh Waktu Penundaan Pengkleman Tali Pusat Terhadap Kadar Hemoglobin Pada Bayi Baru Lahir - Uddin, Rafika (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
Clamping and cutting the umbilical cord is the standard procedure that is always done when the baby is born. The right time to clamp the umbilical cord is still widely debated by experts. The purpose of this research is to know the influence of delay time penglleman umbilical to hemoglobin level in newborn. This type of research is an experimental study with posttest control group design design. The location of the research was conducted at the Bidan Practice Mandiri Setia of Kamonji Puskesmas in Palu in September-October 2017. The population of this study were all newborns in BPM Setia Kota Palu. The samples were 40 newborns consisting of 2 groups of samples, 18 controls infants (2-minute umbilical cord clamp time) and 22 experimental group babies (3-minute cord clamping time). Sampling is done by purposive sampling. Blood collection after umbilical cord clamped and cut from the umbilical vein as much as 2 cc and done in laboratory examination using the tool Hematology Autoanalyzer. Data analysis was done by using average test using independent T-test. The results of the average value of hemoglobin group of 2 minutes amounted to 14.5 g / dl and group 3 minutes of 15.9 gr / dl. Means there is a difference in Hb levels between the time 3 minutes higher than 2 minutes. From the results of independent T-test obtained p value = 0,000, then the value p = 0,000 <Î± = 0.05. It was concluded that the delay time of umbilical cord clashing effect on hemoglobin level in newborn. The research suggestion the need for health workers to evaluate the delay time of umbilical cord clamping used in APN to increase hemoglobin levels in newborns.